168k views
0 votes
-6 - (2x + 7) = -2(x +6) -1

User Nicola
by
5.5k points

2 Answers

5 votes

Answer:

The equation has not solution, both parts of the equation correspond to the same line.

Explanation:

-6 -(2x+7) = -2(x+6) - 1

-6 -2x - 7 = (-2*x + (-2*6)) - 1

-6 - 2x - 7 = -2x - 12 - 1

-2x - 13 = -2x - 13

-2x = - 2x

User Faraaz Kurawle
by
4.9k points
4 votes

Answer:

Infinite solutions

Explanation:

You can put in any number for x and the 2 sides of the equation will equal each other.

-6 - (2x + 7) = -2(x +6) -1-example-1
User ProxyTech
by
5.5k points